Honsberger's bankruptcy in Canada - Honsberger, John D. (Thomson Reuters Canada, 2017)
"In 1922, the first edition of Bankruptcy Law in Canada found pride of place on the shelves of Canadian insolvency practitioners. Now nearly a century later, the new Fifth Edition of Honsberger?s Bankruptcy in Canada is destined to become an invaluable resource for the insolvency community ? a trusted authority for those who deal with bankruptcy problems on a daily basis and those who need occasional guidance. Honsberger?s Bankruptcy in Canada, Fifth Edition is thorough and comprehensive, but also understandable and eminently readable. In clearly written prose, the authors articulate not just the principles, but the history and adaptations underlying the principles, along with practical insight and guidance. Rather than follow the Act section by section, the authors have gathered relevant elements by concept and theme. Practitioners and jurists, with their heavily underlined copies of the previous edition, will welcome both the logical new organization and the updated examination." --publisher's description.